2018
DOI: 10.1093/jac/dky213
|View full text |Cite
|
Sign up to set email alerts
|

Ceftazidime/avibactam versus standard-of-care agents against carbapenem-resistant Enterobacteriaceae harbouring blaKPC in a one-compartment pharmacokinetic/pharmacodynamic model

Abstract: blaKPC-producing organisms demonstrated susceptibility to ceftazidime/avibactam and bactericidal activity was observed in the PK/PD model. Based on these data, ceftazidime/avibactam is a valuable agent for treating KPC-producing organisms and should be considered for treatment of infections caused by these pathogens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 30 publications
0
3
1
Order By: Relevance
“…Interestingly, we observed somewhat limited bacterial killing by CAZ/AVI in the dynamic one-compartment PK/PD model (∼2 log 10 cfu/mL reduction was observed at 48 h). Some previous studies against KPC-producing K. pneumoniae isolates in dynamic PK/PD models showed more killing than we observed in the present study (>5 log 10 cfu/mL killing by 48 h), [45] , [46] while our previous data suggest inter-isolate variations in the rate of killing exist (between 2.5 and 5 log 10 cfu/mL killing by 48 h). [47] However, isolates from the previous in vitro studies were from ST258, were not identified as hypervirulent, and they had lower MICs to CAZ/AVI ranging from 0.125/4 to 0.5/4mg/L (MICs in present study, 4/4mg/L).…”
Section: Discussioncontrasting
confidence: 49%
“…Interestingly, we observed somewhat limited bacterial killing by CAZ/AVI in the dynamic one-compartment PK/PD model (∼2 log 10 cfu/mL reduction was observed at 48 h). Some previous studies against KPC-producing K. pneumoniae isolates in dynamic PK/PD models showed more killing than we observed in the present study (>5 log 10 cfu/mL killing by 48 h), [45] , [46] while our previous data suggest inter-isolate variations in the rate of killing exist (between 2.5 and 5 log 10 cfu/mL killing by 48 h). [47] However, isolates from the previous in vitro studies were from ST258, were not identified as hypervirulent, and they had lower MICs to CAZ/AVI ranging from 0.125/4 to 0.5/4mg/L (MICs in present study, 4/4mg/L).…”
Section: Discussioncontrasting
confidence: 49%
“…But little work has been done to evaluate the efficacy of available antibiotics against heteroresistant strains. Ceftazidime/avibactam, a β-lactam/β-lactamase inhibitor combination, has been proposed as a new salvage therapy for severe KPC-Kp infections (Barber et al, 2018; Manning et al, 2018; Tumbarello et al, 2019). The objective of this study was to evaluate the in vitro effect of ceftazidime/avibactam in combination with polymyxin B against polymyxin B heteroresistance Klebsiella pneumoniae .…”
Section: Introductionmentioning
confidence: 99%
“…Given that both CAZ and AVI are less than 10% bound to plasma proteins, the total concentrations measured were approximated as free concentrations. As the one‐compartment model could perfectly describe the process of distribution and linear elimination for CAZ and AVI in the body, 27,28 t 1/2 and % fT in patients could be calculated based on the C trough and C peak . The optimal PK/PD targets for CAZ and AVI are 50% fT > MIC and 50% fT > C T of 1 mg/L, respectively.…”
Section: Discussionmentioning
confidence: 99%